Keutuhan Surah dalam Struktur Al-Qur'an - Ahmad Solahuddin Dunkring; Jamaluddin Hadi Kusuma (SUHUF, 2020)
In his book Nizam Al-Qur'an wa Ta’wil Al-Furqan bi Al-Furqan, al-Farahi (1863-1930), an Indian scholar, based his ideas on the wholeness of the surah in the structure of the Qur’an based on a number of assumptions: the coherent relationship between one verse and the next verses as well as the inter-connection relationship between one narrative and another in one surah into the wholeness (za wahdaniyyah). This article tries to analyze al-Farahi’s method of interpretation in the form of munasabah al-ayat, nazm, ‘amud and to evaluate his method. The author concludes that al-Farahi’s basic assumption is that the sura is a wholeness. The analytical method is a linguistic approach that includes mufradat (lexicology analysis), nahw (syntax), uslub (stylistics), mawaqi’ at-tadabbur (the place of reflection) and nazm (structure). Al-Farahi made al-Qur’an the primary source, because it interprets one another. Sources of interpretation outside of the Qur’an (hadith, asar and divine books) are secondary sources of interpretation which are positioned below the Qur’an. Al-Farahi concluded that the surah has one mandate, which he later called it as ‘amud. Keywords: Al-Farahi, munasabah, nazm, ‘amud, coherence.